The Impact of the Discovery Learning Model on Mathematical Communication Skills and Study Habits of Junior High School Students - Faridayanti, Iva; Nasrullah, Anton; Hidayat, Amat; Kania, Nia (Edupedia Publisher, 2025)
This study investigates the impact of the discovery learning model on students' mathematical communication skills and learning habits in junior high school. Motivated by low mathematical communication abilities and limited use of varied teaching methods, this research aims to assess learning outcomes, the effect of discovery learning, and students' study habits. Using an experimental design (One Group post-test design), 26 seventh-grade students from SMP Negeri 2 Cinangka were selected via simple random sampling. Data were collected through a mathematical communication skills test (5 questions) and a learning habits questionnaire. Prerequisite tests (normality and homogeneity) and hypothesis testing (Independent Sample t-test) were conducted for analysis. Results revealed that the experimental class achieved an average mathematical communication score of 66.83, compared to 60.00 in the control class. Hypothesis testing showed a significant effect (p = 0.04 < α = 0.05). Additionally, the learning habits questionnaire indicated a 65% positive response. The findings demonstrate that the discovery learning model significantly enhances students' mathematical communication skills and fosters strong study habits. This study highlights the effectiveness of discovery learning in improving educational outcomes and suggests its potential for broader application in mathematics education.